Pengaruh Pembelajaran Sejarah Kebudayaan Islam terhadap Pengembangan Karakter Siswa di MTs Negeri Kota Bogor - Wilda Lailatul Mukaromah; Moh. Romli (Jurnal Dirosah Islamiyah, 2025)
This research is based on the background that shows that there are still some students who have problems in discipline, responsibility for their duties, lack of manners to teachers, and lack of reflection of Islamic values in dressing and speaking. This research was carried out at MTs Negeri Bogor City. The purpose of the study is to explain how learning Islamic Cultural History (SKI) and character development of students, as well as to find out whether there is an influence of learning Islamic Cultural History (SKI) on student character development, in MTsN Bogor City This research uses a quantitative method. The research instrument used questionnaires given to students, and the data obtained was analyzed with the help of the SPSS version 29 application with the product moment correlation analysis technique. The population in this study was 954 students and used 64 students as a research sample. The results of the analysis showed that r-count was 0.580 > r-table was 0.254, therefore H0 was rejected and Ha was accepted, which means that there is an influence of learning Islamic cultural history on the development of students' character. Likewise, the significance test with the t-test with a t-test result of 5.611 > t table 1.669. Therefore, the influence of learning Islamic cultural history on the development of students' character is significant, while the contribution of Islamic cultural history learning to student character development is shown by KD (Coefficient of Determination) = 0.337 which means that learning Islamic cultural history contributes 33.7% to student character development.